TRADISI MASYARAKAT SEBAGAI KEKUATAN SINKRETISME DI TRUCUK, KLATEN - Sutiyono Sutiyono (LPPM UNY, 2011)
This study aims to prove that the societal tradition in in Trucuk alive and growing dynamically, because of the strength of syncretism. This research was conducted in rural areas Trucuk District, Klaten, Central Java. The time to conduct field studies began in March to October 2006. As a research subject, namely: farmer, caretaker shrine, the pilgrims, paranormal, dalang, arts reog elders, chairman slawatan, modin, lurah, Muhammadiyah activists, political elites, religious teachers, kyai, mubaligh, congregational recitation, and the priest mosque. Methods of data collection is participant observer, depth interviews, and study of documentation. This study uses an ethnographic approach. The results showed that the societal tradition who are still be regularly performed of rural communities is slametan. Slametan an intangible form of social activism traditional ceremony which was attended by a group of people from different social groups to come together, accompanied by a serving dish and prayed the Islamic way. In gathering together, all of them understand each other and can understand each other. The discrepancies in all respects to be thin and fixed on the formation of community integration or syncretism. The strength of syncretism make the societal tradition in Trucuk alive and growing dynamically. So, the theory mentions that syncretism is the attempt to unify the different sects (Mulder, 1992) proved in this study